2016
DOI: 10.1007/s40719-016-0061-z
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Combat Trauma

Abstract: Purpose of review Military physicians have amassed tremendous experience treating children with combat-related injuries in Iraq and Afghanistan. This review will present several treatment principles adapted from adult trauma care that were applied to children in war and consider their selective application in civilian practice. Recent findings Many standard practices of adult trauma care were applied to the management of war-injured children. Initial reports of tourniquet use, tranexamic acid administration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
(42 reference statements)
1
5
0
1
Order By: Relevance
“…Borgman et al 6 found that compared with adults, pediatric patients had a significantly worse outcomes with higher Injury Severity Scores (ISS), worse Glasgow Coma Scale (GCS) scores, younger than 8 years, being female, and having burns. The high-resource consumption after burn injuries noted by Borgman was similar to the findings by Gurney et al The age range of children treated spanned 2 days to 18 years old 7 . Children younger than 3 years had the lowest encounter rate, but those 2 years or below had the highest mortality rate (25.1%) 2,8 .…”
Section: Discussionsupporting
confidence: 78%
“…Borgman et al 6 found that compared with adults, pediatric patients had a significantly worse outcomes with higher Injury Severity Scores (ISS), worse Glasgow Coma Scale (GCS) scores, younger than 8 years, being female, and having burns. The high-resource consumption after burn injuries noted by Borgman was similar to the findings by Gurney et al The age range of children treated spanned 2 days to 18 years old 7 . Children younger than 3 years had the lowest encounter rate, but those 2 years or below had the highest mortality rate (25.1%) 2,8 .…”
Section: Discussionsupporting
confidence: 78%
“…Поранення дітей внаслідок бойових дій не часто описують у наукових публікаціях внаслідок рідкісності таких випадків. Лікування поранених дітей, як показав досвід проведення бойових дій в Іраку й Афганістані, здебільшого потребує умов інтенсивної терапії [1] та високого професіоналізму лікарів [2], адже травми, пов'язані з війною, як правило, є більш тяжкими, ніж у цивільному секторі [3], мають вищу смертність, ніж небойові травми чи інші госпіталізації [4,11].…”
Section: вступunclassified
“…The use of adult equipment is often necessary, and despite limitations it may still achieve good results. Reports from military medical teams in Afghanistan and Iraq demonstrated good control of traumatic haemorrhage in children when using adult-sized tourniquets and full-dose tranexamic acid in lieu of paediatric equipment and dosing regimens 5. Access to paediatric-specific equipment remains preferable, however, and ensures the best possible care can be delivered without needing to use improvised solutions.…”
Section: Interventionsmentioning
confidence: 99%
“…For example, the surgical approach in US military field hospitals for those presenting with mangled lower extremities during conflicts in Iraq and Afghanistan was influenced by the long-term care that was likely to be available to the patient. US service personnel usually had better outcomes following early amputation as they had ongoing rehabilitation available to them; however, the treatment for local children presenting with similar injuries was focused on limb salvage 5. One review considered 16 papers published by various civilian and military surgical teams that treated children and adults following a range of disasters between 1990 and 2018 8.…”
Section: Interventionsmentioning
confidence: 99%